Nature as guide: Wittgenstein and the renewal of moral theology - Goodill, David (The Catholic University of America Press, 2022)
"The author provides starting points for a conversation between Wittgenstein and moral theology, using metaphysics and the philosophy of nature in the service of theology to illuminate one's life in Christ. Most of the theologians discussed are influenced by the tradition of Christian ethics found in Scripture and the church fathers"--